Culture trumps structure in the competitive struggle between teaching and research - De Klerk, Danie; MacGregor, Agatha; Benvenuti, Susan (Axiom Academic Publishers, 2022)
In response to international research-informed calls for the professionalisation of teaching to support student success, the South African Higher Education sector has implemented structures aimed at promoting teaching and research as equals. Despite this occurring at both the institutional and national level, many South African institutions are still struggling to achieve this balance, with research remaining a dominant factor in academic recognition. Using a phenomenographic research design and employing the notion of structure, culture and agency to conduct a thematic analysis of qualitative data, this study examines the success of a potentially enabling structure (i.e., a Postgraduate Diploma in Education [Higher education]) designed to professionalise teaching in support of student success. The findings suggest that, despite strong indications that good teaching is encouraged and valued, the dominant research culture within the authors’ institution has negated the attempts to place research and teaching on an equal footing. Institutional-level structures remain fragmented with respect to research and teaching. Student success is not only dependent on receiving research-informed disciplinary knowledge, but also on how an institution promotes and facilitates well-informed and scholarly teaching practices. The authors conclude by recommending i) the recognition of postgraduate diplomas as an indicator of learning and teaching expertise by staffing and promotions committees; ii) the utilisation of agents who have self-selected to professionally develop their teaching to be part of a coherent system that supports and steers cultural change within academia; and iii) the recognition of research in learning and teaching as equal to discipline-specific research.
Chapter 4